Ikhtikar dalam Tinjauan Ekonomi Islam (Studi Pasar Merapi Seputih Mataram Lampung Tengah) - Mahfud (Institut Agama Islam Agus Salim Metro Lampung, 2022)
Unfair competition causes strong groups (corporations) to get stronger. Injustice is often perpetrated in various markets in Indonesia. This also happened to the Merapi Seputih Mataram market, Central Lampung Regency. There are various ways that traders do at the Merapi market. One of them is buying up goods to be held/hoarded, to be sold at high prices. Ikhtikar carried out by traders and agents to gain large profits has harmed society and is a disgraceful act that is condemned in Islam. This act is an act of injustice and prohibition in Islam. The efforts made by traders and agents in Merapi has harmed the surrounding community. This act disturbs society and causes social imbalance. This act has caused a shortage of goods and caused prices to rise more than 150% of the normal price. The Fuqaha forbid and forbid ikhtikar because this is a deviation from Islamic values and is an act of persecution that harms fellow human beings.